Üsküdar bölgesinde birinci basamağa kayıtlı 40 yaş ve üstü populasyonda multimorbidite prevalansı - Karahan, Ömer (My University, 2015)
Giriş ve Amaç 21. yüzyılda kronik hastalıkların oluşturduğu küresel yük büyümeye devam etmektedir.Çok sayıda kronik hastalığa sahip olmak, hastanın işlevselliğini ve yaşam kalitesini azaltır, sağlık harcamalarını arttırır. Ayrıca, özgül sağlık bakımı gerektirebileceğinden hastanın yönetimini daha da zorlaştırır. Multimorbidite,kişide iki ya da daha fazla kronik durumun, hastalığın eşzamanlı olarak bulunmasıdır. Multimorbiditenin epidemiyolojisini anlamak; müdahale imkanlarını geliştirmek, hastalık yükünü azaltmak, önlemek ve sağlık hizmetlerini hastaların ihtiyaçları doğrultusunda düzenlemek açısından çok önemlidir .Ülkemizde spesifik bazı kronik hastalıklar için yapılmış prevalans çalışmaları olmakla birlikte bu araştırmalar toplumdaki multimorbidite sıklığını yansıtmamaktadır. Çalışmanın amacı İstanbul ili Üsküdar ilçesinde Aile Sağlığı Merkezlerine (ASM) kayıtlı 40 yaş ve üzeri bireylerde multimorbidite prevalansını saptamaktır. Yöntem Hastalar İstanbul ili Üsküdar ilçesi Aile Sağlığı Merkezlerine kayıtlı 40 yaş ve üzeri tüm bireylerden tabakalı örneklem yöntemiyle seçilmiştir. Hastaların sadece multimorbidite durumlarına ait bilgileri doktorlardan istenmiştir. Hastaların son bir senede gerçekleştirdikleri ASM ve hastane ziyaretleri, hastalara konulan teşhisler ve reçete edilen ilaç etken maddeleri kayıt altına alınmıştır. İlaç etken maddeleri, herhangi bir hastanın aldığı tanıya yönelik ilaç kullanımının olup olmadığını tespit amacıyla kayıt altına alınmıştır. Prevalans hesaplamasında; ilaç tedavisi teyit edilmiş olan tanılar dikkate alınmıştır. Bulgular Çalışmaya dahil olan 1187 bireyde multimorbidite prevalansı % 27,8 (n=330) bulunmuştur. Kadınlarda multimorbidite prevalansının erkeklerden istatiksel olarak anlamlı şekilde yüksek olduğu saptanmıştır. (E: % 19,5 n=115 , K: % 36,1 n=215 x2=40,81 p<0,001) 65 yaş ve üstü hastalarda multimorbidite prevalansı anlamlı olarak yüksek tespit edilmiştir. (65>y % 19,5 n=179, 65<y % 55,9 n=151 x2=137,73 p<0,001) Hipertansiyon % 26,8 (n=318) hastada tespit edilmiş olup çalışma bölgemizde en sık rastlanan hastalık olarak saptanmıştır. iii Multimorbid hastalar bir yıl içerisinde ASM ve hastanelere multimorbid olmayan hastalara göre daha fazla ziyaret gerçekleştirmişlerdir. (ASM: multimorbid; 7,01 n=292 , multimorbid olmayan; 1,6 n:818 t:26,13 p<0,001) (Hastane: multimorbid; 5,5 n=288, multimorbid olmayan 2,1 n=807 t:11,30 p<0,001) Sonuç Çalışmamızda bulduğumuz multimorbidite prevalansı, 40 yaş ve üstü her 4 bireyden birinin multimorbidite ile mücadele ettiğini göstermektedir. Kadınlarda ve 65 yaş üstü bireylerde bu oran ciddi artış göstermektedir. Multimorbiditeli hastalar, hastanelere kıyasla ASM’leri daha sık ziyaret etmektedirler. iv

Introduction and Objectives In the 21st Century, the global burden of chronic diseases continues to grow. Having a large number of chronic diseases impairs the patient's functioning and reduces the quality of life while increasing the health cost (Chronic diseases are associated with impaired functioning and reduced quality of life as well as increased health/ medical costs for the patient). In addition, it complicates the management of the patient as these conditions may all require specific medical care. Multimorbidity is defined as the simultaneous presence of two or more chronic conditions in a person. Understanding the epidemiology of multimorbidity is great importance in determining the means of intervention, reducing the burden of disease and providing the most appropriate medical care according to the needs of the patient. Although there are prevalence studies on certain specific chronic diseases in Turkey, they do not reflect the frequency of multimorbidity in the overall society. The aim of this study is to determine the multimorbidity prevalence for the patient population aged 40 and over that are currently registered at all the family health centres (FHC) in the suburb of Uskudar, Istanbul. Method The case population for the study has been chosen by using the stratified purposeful sampling method among the individuals aged forty and over registered at family health centres in the suburb of Uskudar in Istanbul . Only the details concerning the multimorbidity of patients have been requested from the treating physicians. The FHC and hospital visits over the past one year as well as the diagnosis and the pharmacologically active compounds of medications prescribed at these visits have been recorded. The purpose in registering the prescriptions was to determine if the drug choice was appropriate for the treatment of proposed diagnoses. In the calculation of prevalence, only the diagnoses with confirmed appropriate pharmaceutical treatments have been taken into account. Findings The study included 1187 cases and the multimorbidity prevalence is found to be %27,8 (n=330). The prevalence for females is shown to be higher and this difference is statistically meaningful (E: %19,5 n=115, K: % 36,1 n=215 x2=40,81 p<0,001). v The patient population of 65 years of age and over also had a statistically significant increase in multimorbidity (65>y % 19,5 n=179, 65<y % 55,9 n=151 x2=137,73 p<0,001 ). Hypertension (HT) is demonstrated to be the most prevalent condition with a percentage of 26.8 (n=318) of the population being treated for HT during the course of the study. There was an increased frequency of visits to family health centers and hospitals annually from multi-morbid patients compared to the rest of the population. (FHC: with multimorbidity; 7,01 n=292, without multimorbidity; 1,6 n= 818 t: 26,13 p<0,001) (Hospitals: with multimorbidity; 5,5 n=288, without multimorbidity; 2,1 n=807 t: 11,30 p<0,001). Results In this study, the prevalence of multimorbidity highlights that one in four people in the age group of 40 and over struggles with multimorbidity in the general population. This ratio is significantly higher for females and for the age group of 65 and over. Multimorbid patients visit family health centers more often than the hospitals.
Keywords: Aile hekimliği; Aile sağlığı